2011
DOI: 10.1007/s11302-011-9254-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of purinergic signaling on nitric oxide production by neutrophils stimulated with Trichomonas vaginalis

Abstract: Trichomonas vaginalis is a parasite from the human urogenital tract that causes trichomonosis, the most prevalent non-viral sexually transmitted disease. The neutrophil infiltration has been considered to be primarily responsible for cytological changes observed at infection site, and the chemoattractants can play an important role in this leukocytic recruitment. Nitric oxide (NO) is one of the most widespread mediator compounds, and it is implicated in modulation of immunological mechanisms. Extracellular nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In general, the anti-inflammatory effects of adenosine are attributed to A2A receptor based on its ability to increase cAMP accumulation [43]. The involvement of this receptor subtype was also observed in one previous study of our group where A2A was associated with reduction of NO production by T. vaginalis-stimulated neutrophils [11]. In the present study, the participation of A1 receptor was suggested by the overexpression of the receptor fluorescence in the presence of increased adenosine bioavailability.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In general, the anti-inflammatory effects of adenosine are attributed to A2A receptor based on its ability to increase cAMP accumulation [43]. The involvement of this receptor subtype was also observed in one previous study of our group where A2A was associated with reduction of NO production by T. vaginalis-stimulated neutrophils [11]. In the present study, the participation of A1 receptor was suggested by the overexpression of the receptor fluorescence in the presence of increased adenosine bioavailability.…”
Section: Discussionsupporting
confidence: 86%
“…Considering the involvement of purinergic signaling on this immune mechanism, the presence of nucleotides did not regulate the release of the mediator. Previous work from our group has already demonstrated the participation of nucleotides and nucleosides on the NO secretion by T. vaginalis-stimulated neutrophils [11]. Interestingly, the nucleoside adenosine by itself was not able to modulate ROS production by T. vaginalis-stimulated neutrophils.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Neutrophils exposed to Trichomonas vaginalis produced nitric oxide and interleukin-8. 90,91 Interleukin-8 along with the other cytokines can, in turn, stimulate NO synthesis.…”
Section: Protozoan Parasites Initiate the Development Of Finger-like mentioning
confidence: 99%
“…On the contrary, nucleosides as adenosine, often suppress the inflammatory response, limiting local and systemic inflammation . In T. vaginalis , this enzymatic cascade has already been characterized with the presence of nucleoside triphosphate diphosphohydrolase (NTPDase) and ecto‐5′‐nucleotidase enzymes, and it seems to be involved in mediating immune aspects during infection …”
Section: Introductionmentioning
confidence: 99%